Pengaruh Sukrosa dan Fotoperiode terhadap Embriogenesis Somatik Jeruk Keprok Batu 55 (Citrus reticulata Blanco.) - Wahyu Widoretno; C. Martasari; Nirmala FD (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2013)
ABSTRACTThis study aimed at determining the effect of sucrose and photoperiod treatment on the growth and development of somatic embryos in citrus Keprok Batu 55. Citrus somatic embryos were induced from nusell us explants cultured on MT (Murashige and Tucker) medium + 146 mM sucrose + 500 mg L- 1malt extract. After 3 times subcultures, somatic embryos were cultured on medium with several concentrations of sucrose (146, 171, 196, and 246 mM) or treated with different photoperiod (8, 12, and 16 hours). Treated somatic embryos were regenerated into plantlets. The research results showed that the addition of sucrose on medium did not affect on fresh weight of somatic embryo at 2 weeks of culture but decreased the fresh weight of somatic embryos at 4 weeks of culture. The higher the sucrose added to the medium, the more embryo somatic fresh weight decrease.Induction and growth of s omatic embryo was also influenced by culture conditions. Fresh weight of somatic embryos was cultured with photoperiod 12 hours day- 1for 2 and 4 weeks higher than the fotoperiode 8 hours day- 1. However, the fresh weight of somatic embryos decreased if photoperiod was increased to 16 hours day- 1. Induced somat ic embryos on medium containing high sucrose ( 246 mM) produced more plantlets with higher size than those with low sucrose. Somatic embryos cultured with photoperiod 12 hours day-1produced more plantlets than those of photoperiod 8 and 16 hours day-1. Nevertheless, the somatic embryos were cultured with photoperiod 16 hours day-1produced plantlets with higher sizes than photoperiod 8 and 12 hours day- 1.Keywords: medium, Murashige and Tucker, nuselus, plantletABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh perlakuan sukrosa dan fotoperiode terhadap pertumbuhan dan perkembangan embrio somatik jeruk Keprok Batu 55. Embrio somatik diinduksi dari eksplan nuselus yang dikultur pada medium MT (Murashige dan Tucker) + sukrosa 146 mM + ekstrak malt 500 mg L-1. Setelah 3 kali subkultur, embrio somatik dikultur pada media MT dengan penambahan beberapa konsentrasi sukrosa (146, 171, 196, dan 246 mM) atau diperlakukan dengan fotoperiode yang berbeda (8, 12, dan 16 jam hari- 1). Embrio somatik hasil perlakuan selanjutnya diregenerasikan menjadi planlet. Hasil penelitian menunjukkan penambahan sukrosa pada medium tidak berpengaruh terhadap bobot basah embrio somatik pada umur kultur 2 minggu tetapi menurunkan bobot basah embrio somatik pada umur kultur 4 minggu. Semakin tinggi sukrosa yang ditambahkan dalam medium , penurunan bobot basah embrio somatik juga semakin meningkat. Induksi dan pertumbuhan embrio somatik juga dipengaruhi oleh kondisi kultur. Bobot basah embrio somatik yang dikulturkan selama 2 dan 4 minggu dengan fotoperiode 12 jam hari- 1lebih tinggi dibandingkan dengan fotoperiode 8 jam hari-1. Namun demikian apabila fotoperio de ditingkatkan menjadi 16 jam hari- 1, bobot basah embrio somatik mengalami penurunan. Embrio somatik yang diinduksi pada medium yang mengandung sukrosa tinggi (246 mM) mampu beregenerasi menjadi planlet lebih banyak dan berukuran lebih tinggi dibandingkan dengan sukrosa rendah. Embrio somatik yang dikultur dibawah fotoperiode 12 jam hari- 1menghasilkan planlet lebih bany ak dibandingkan fotoperiode 8 dan 12 jam hari-1. Namun demikian, embrio somatik yang dikultur dengan fotoperiode 16 jam hari- 1mampu menghasilkan planlet yang berukuran lebih tinggi dibandingkan dengan fotoperiode 8 dan 12 jam hari-1.Kata kunci: medium, Murashige dan Tucker, nuselus, planlet